PERANCANGAN DAN IMPLEMENTASI SISTEM PENGELOLAAN DANA DONASI PADA YAYASAN KEMANGGISAN BERBASIS WEB DENGAN METODE WATERFALL - Muhammad Rizki; Mundirin; Purwanto (IONTech Journal, 2026)
Donation fund management at Kemanggisan Foundation is still handled manually using Microsoft Excel, making it inefficient, error-prone, and difficult to access outside the foundation. In addition, donors must visit the foundation in person to donate, which is inconvenient. This study aims to design and implement a web-based donation fund management system to facilitate recording of income and expenses, generating financial reports, and enabling donors to donate online. The system was developed using the Waterfall model through requirement analysis, design, implementation, testing, and maintenance phases. The system was designed using UML, implemented using PHP and MySQL, and tested using Blackbox Testing. The results show that the system can manage income, expenses, and financial reports automatically. User evaluation using a Likert questionnaire involving 45 respondents achieved a satisfaction score of 85.44% (strongly agree category), indicating that the system improves efficiency, accuracy, and donor convenience.